2022
DOI: 10.3390/ijms232012697
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Sheet Engineered Using Human Umbilical Cord-Derived Mesenchymal Stem Cells Improves Diabetic Wound Healing

Abstract: Diabetic foot ulceration is a common chronic diabetic complication. Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) have been widely used in regenerative medicine owing to their multipotency and easy availability. We developed poly(lactic-co-glycolic acid) (PLGA)-based scaffold to create hUC-MSC tissue sheets. In vitro immunostaining showed that hUC-MSC tissue sheets formed thick and solid tissue sheets with an abundance of extracellular matrix (ECM). Diabetic wounds in mice treated with or with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Numerous studies have highlighted the ability of iPSC-CMs to engraft, establish a functional myocardium, and further improve the cardiac function in diverse animal models of MI [ 22 , 32 ]. PLGA is a biodegradable and biocompatible copolymer that has been used in FDA-approved therapeutic devices including several in our previous studies [ 16 , 18 , 19 , 24 , 25 , 33 ]. Our previous studies have demonstrated that constructing and organizing hiPSC-CMs into tissue sheets using PLGA fiber scaffold in vitro could enhance their therapeutic capabilities after transplantation [ 17 , 19 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies have highlighted the ability of iPSC-CMs to engraft, establish a functional myocardium, and further improve the cardiac function in diverse animal models of MI [ 22 , 32 ]. PLGA is a biodegradable and biocompatible copolymer that has been used in FDA-approved therapeutic devices including several in our previous studies [ 16 , 18 , 19 , 24 , 25 , 33 ]. Our previous studies have demonstrated that constructing and organizing hiPSC-CMs into tissue sheets using PLGA fiber scaffold in vitro could enhance their therapeutic capabilities after transplantation [ 17 , 19 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…To quantify the density of neovessels and arterioles in the graft and the MI border zone of host, von Willebrand Factor (vWF) and alpha-smooth muscle actin (α-SMA) were used to stain the endothelial cells and vascular smooth muscle cells, respectively, while cell nuclei were counterstained blue for DAPI. The neovessels were represented by orange staining, and orange/green double staining represented arterioles, as previously reported [ 25 ]. Images were captured using a confocal microscope (Nikon A1, Nikon, New York, NY, USA) and analyzed with ImageJ software (NIH, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations